Pencegahan dan Asuhan Gizi Anak Balita Wasting di Wilayah Kerja Puskesmas Taman Bacaan Palembang - Afriyana Siregar; Yuli Hartati; Podojoyo Podojoyo; Imelda Telisa (Poltekita: Jurnal Pengabdian Masyarakat, 2022)
The results of the study on the nutritional status of children under five in Indonesia were stunted 24.4%, wasted 7.1%, and underweight 17.0%. The purpose of this activity was to increase knowledge of maternal nutrition and nutritional care for wasting children under five. This activity provided material with counselling to several groups of mothers under five with two counselling sessions for 1 month (together with the pre-test) followed by monitoring & evaluation (Posttest of nutritional knowledge). The method used was counselling using booklets and leaflets related to wasting and nutritional care. Increased knowledge of maternal nutrition & weight gain of toddlers is an illustration of the success of the activity. The nutritional knowledge of mothers under five was mostly good (nutritional knowledge post test results improved from the pretest), while the results of measuring the weight & height of some toddlers in wasting old cases had increased in normal nutritional status, while some nutritional status of toddlers was malnourished increased to wasting. The Puskesmas was helped by this activity & asked the Community Service team to carry out this routine activity in their puskesmas area. ABSTRAK Hasil studi status gizi Indonesia tentang prevalensi Balita di Indonesia yaitu stunted (24,4%), wasted (7,1%), underweight (17,0%). Tujuan kegiatan ini meningkatkan pengetahuan gizi ibu dan asuhan gizi anak balita wasting. Kegiatan ini memberikan materi dengan penyuluhan kepada beberapa kelompok ibu balita sebanyak dua kali penyuluhan selama 1 bulan (bersamaan dengan pretest) berikutnya diadakan monitoring & evaluasi (posttest pengetahuan gizi). Adapun metode yang digunakan yaitu penyuluhan menggunakan booklet dan leaflet terkait wasting dan asuhan gizi ada peningkatan pengetahuan. Peningkatan pengetahuan gizi ibu & kenaikan berat badan balita merupakan gambaran keberhasilan kegiatan. Pengetahuan gizi ibu-ibu balita sebagian besar sudah baik (hasil posttest pengetahuan gizi meningkat dari pretest), sedangkan hasil pengukuran berat badan & tinggi badan balita beberapa balita wasting kasus lama sudah meningkat di status gizi normal, sedangkan beberapa status gizi balita gizi buruk meningkat wasting. Pihak Puskesmas terbantu dengan kegiatan ini & meminta kembali tim Pengabdian masyarakat untuk melakukan kegiatan rutin ini di wilayah puskesmas mereka.